Analysis of Underground Cable Fault Techniques Using MATLAB Simulation - Muhammad Suhail Shaikh; Muhammad Mohsin Ansari; Munsif Ali Jatoi; Zahid Ali Arain; Aleem Ahmed Qader (Sukkur IBA Journal of Computing and Mathematical Sciences, 2020)
In populated areas, underground cables are using for Electrical distribution and transmission purposes, due to this, underground cables have more advantages than overhead transmission line during abnormal weather condition including rain, and thunderstorm. But calculation and determination of the exact position of fault location occur, have been a significant challenge in the underground. In this paper, different techniques like Sectionalizing, thumper, and time domain reflectometry and MATLAB simulation technique-based reusing for determining fault location in underground cable systems and the also factors that affect the fault location are discussed.